An algebraic approach to identifying bottlenecks in linear process models of multifunctional energy systems - Tan, Raymond Girard R. (Animo Repository, 2012)
This paper presents an algebraic approach for identifying bottlenecks in continuous process systems where each process unit is characterized by fixed mass and energy balance relationships. In industrial applications, such a system is designed to produce a particular product portfolio. This is determined from the anticipated products market and is taken as a baseline state. A process plant is designed with the individual process units at the required size to meet the baseline portfolio, and typically additional margin for safety reason is considered. A simple approach to identify the bottlenecks is proposed and the product portfolio is changed by a given fraction relative to the baseline state. A bottleneck occurs when the available excess capacity of a process unit is insufficient to meet the incremental requirement. Two illustrative case studies demonstrate the proposed methodology. © 2012 Pleiades Publishing, Ltd.